EFEKTIVITAS TEKNIK PENGANDAIAN DIRI DALAM PEMBELAJARAN MENULIS CERITA PENDEK - Suardi Zain; M. Nurzin R. Kasau; Suhartini Suhartini (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
The Effectiveness of Self Assignment Technique to the Ability of Writing Short Story. This study aims to describe the effectiveness of self-prescribing techniques on the ability to write short stories. This research is a quantitative research that try to apply self-prescribing technique in writing short stories. Data collection techniques used in this research are documentation and writing skill. The data analysis technique used is descriptive statistical techniques in the form t-tes. The results of data analysis in this study indicate that the self-efficacy technique is effective on the ability to write short stories in the seventh grade students of SMP.